The Role of Preoperative Steroids in Atraumatic Cochlear Implantation Surgery. Issue 8 (September 2017) - Lo, Jonathon; Campbell, Luke; Sale, Phillip; Chambers, Scott; Hampson, Amy; Eastwood, Hayden; O'Leary, Stephen
Abstract : Hypothesis: Depth of insertion is related to the extent of tissue response and low frequency hearing loss. Intravenous steroids have greatest effect in reducing postimplantation fibrosis and hearing loss in the presence of significant electrode insertion trauma, when compared with saline treatment. Background: Experiments exploring the enhancement of cochlear implantation (CI) outcomes with glucocorticosteroids have produced mixed results, possibly due to lack of standardization of the CI model. Methods: Forty-eight normal-hearing guinea pigs were randomly implanted with a highly flexible electrode to a depth of 1.5, 3.0, or 5.0 mm. For each insertion depth, sub-cohorts received either intravenous saline ("saline") or dexamethasone ("steroid") 60 minutes before implantation. Shifts in electrocochleography thresholds at 2 to 32 kHz were determined before and 4 weeks after implantation. Cochleae were harvested and imaged. Results: Low-frequency hearing loss was greatest with 5.0 mm insertions. Fracture of the osseous spiral lamina and/or fibrotic involvement of the round window membrane exacerbated hearing loss. The extent of intracochlear fibrosis was directly related to the depth of insertion. Steroids reduced the intracochlear tissue response for deepest insertions and in apical regions of the cochlea where basilar membrane contact was prevalent. Steroids preserved no more hearing than saline at all insertion depths. Conclusion: Cochlear trauma influenced postimplantation hearing loss and steroid effect on fibrosis. Fibrosis, and to a lesser extent, postimplantation hearing loss increased proportionally to the depth of insertion. Steroids did not influence fibrosis relating to the cochleostomy, but could reduce scarring as the electrode negotiated the hook region or near the electrode tip.